Genes relacionados à virulência, resistência aos antimicrobianos, filogrupos genéticos e resposta imunoinflamatória associadas com cepas de Escherichia coli enteroagregativa isoladas de crianças nutridas e desnutridas em Fortaleza-Ce, Brasil - Amaral, Marília Silveira Maia Gurgel do (2018)
Child malnutrition is one of the causes of increased morbidity and mortality among children in developing countries. Infections with enteroaggregative Escherichia coli, independent of symptomatology, have been associated with a growth deficit of these children.The objective of this study was to investigate the genes related to virulence, antimicrobial resistance, genetic phylogroups and immunoinflammatory response associated with strains of EAEC isolated from nourished and malnourished children in Fortaleza, Ceará, Brazil. This case-control study was part of a multicenter study entitled "Etiology, Risk Factors and Interactions of Enteric Infections and Malnutrition and the Consequences for Children's Health," or MAL-ED study, which occurred from August 2010 to September of 2013, obtaining approval by the Committee of Ethics in Research of the Federal University of Ceará(COMEPE nº. 246/09).A total of 402 children between the ages of 6 and 24 months were analyzed, with 201 cases children and 201 controls, where the cases were defined as malnourished children through WAZ <-2 and controls were defined as nourished children with WAZ ≥ -1.DNA extractions were performed of Escherichia coli colonies derived from faecal samples from 402 children. Through multiplex PCR five pathotypes of E. coli were detected, diagnostic of the EAEC pathotype was by detection of target genes aatAand aaiC.Detection of genes related to the virulence of EAEC was performed using five multiplex PCR panels, totaling 20 genes. The investigation of the phylogroup A, B1, B2 and D was performed through the search of the genes chuA, yjaA and TspE4C2. The determination of the biofilm formation of these strains was performed through violet crystal staining. To evaluate the antimicrobial susceptibility, CLSI (2017) was used as a parameter. Biomarkers analysis of inflammation were performed using an enzyme-linked immunosorbent assay.Were diagnosed 24.1% (97/402) samples positive for EAEC, where 56.7% (55/97) were defined as cases and 43.3% (42/97) were controls. The most prevalent genes related to virulencein all samples were orf3 and agg3/4C with 81.9% (68/83), followed by aggR with 79.5% (66/83). Those with the lowest prevalence were aafA 28.9% (24/83), followed by aafC 15.6% (13/83) and finally the agg3A with 6% (5/83). None of the genes were correlated with the case or control group. In the distribution of the phylogroups, the philogroup B2 was the most prevalent with 54.2% (51/94), followed by the filogroup D with 38.3% (36/94) and the philogroup A with 7.4% (7/94). In the detection of biofilm formation, the case group obtained a higher formation compared to the control group (45.7% vs 32.9%) and when correlated with the genes related to virulence, the aar gene was associated with biofilm formation (P = 0.0466). In the determination of antimicrobial resistance, ampicillin presented the highest resistance rate with 58.5% (55/94), followed by trimethoprim/sulfamethoxazole with 55.3% (52/94) and azithromycin with 23.5% (23/94).The highest antimicrobial susceptibility rates were presented by ceftazidime with 100% (94/94), followed by cefoxitin, ertapenem and ciprofloxacin with 98.9% (91/94). The biomarkers of systemic inflammation FABP-I (P = 0.0127), IgA anti-LPS (P = 0.0353), IgG anti-LPS (P = 0.0192) were associated with cases of malnutrition. And the biomarkers of inflammation MPO (P = 0.0169), calprotectin (P = 0.0096), CD14s (P <0.0001), SAA (P <0.0001) were associated with the controls.It is concluded that the heterogeneity of EAEC can influence its relation with the host, causing its persistence during colonization, besides the high prevalence of the circulation of strains resistant to several antimicrobials, which makes difficult the treatment of the infection.